Separate and cumulative effect of risk and protective factors associated with suicidal ideation among Chinese infertile couples: a cross-sectional study - Chen, Jijie; Li, Jieke; Liu, Yaqiong; Song, Xiuqing; Yuan, Xiaoyan; Zhang, Xuekun; Deng, Xiaoling (Frontiers in Psychology, 2025)
PurposeThis study was designed to explore separate and cumulative effects of fertility-related pressure, anxiety, depression, resilience and marital quality on suicidal ideation in Chinese infertile couples.MethodsA cross-sectional study was conducted among infertile couples at the reproductive medicine center. Suicidal ideation was evaluated using item 9 of PHQ-9. A score of 1 or above indicated the presence of suicidal ideation. The Fertility Problem Inventory, Generalized Anxiety Disorder-7, Patient Health Questionnaire-8, the 10-item Connor-Davidson Resilience Scale and Quality of Marriage Index were used to measure the risk and protective factors. Risk factor index is used to represent the number of risk factors, and protective factor index is used to represent the number of protective factors.ResultsA total of 674 infertile couples participated this study. 65 infertile men and 76 infertile women reported suicidal ideation. Univariate analysis revealed that infertility-related pressure, anxiety, depression, resilience and marital quality were associated with suicidal ideation in both genders. Binary logistic regression revealed positive associations of risk factor index with suicidal ideation in couples (males: OR = 1.966, 95%CI: 1.636–2.363; females: OR = 2.484, 95%CI: 1.992–3.098). The protective factor index was significantly associated with reduced suicidal ideation odds in females (OR = 0.530, 95%CI: 0.316–0.888), but no significant association was found in males (p = 0.159).ConclusionOur findings indicate that infertility-related pressure, anxiety, depression, resilience and marital quality are associated with suicidal ideation among infertile couples. Specifically, higher risk factor index is linked to increased odds of SI in both genders, with females showing a stronger association. And higher protective factor index is associated with reduced odds of SI in females, though this effect is not significant in males. Therefore, interventions targeting the reduction of infertility-related pressure, anxiety, and depression, coupled with the enhancement of resilience and marital quality, may effectively mitigate the risk of suicidal ideation in this population.